Hubungan Antropometri Tubuh Tinggi Badan Berat Badan Dan Panjang Lengan Terhadap Kemampuan Shooting Free Throw Pada Pemain Basket Di Sd Budya Wacana Yogyakarta - Jaenis Stefanus Duha; Dody Tri Iwandana (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
This study aims to: determine and analyze the relationship between body anthropometric variables (including height, weight, and arm length) to the ability to shoot free throws in students who participate in extracurricular basketball at SD Budya Wacana Yogyakarta. This study is a quantitative study. The population used in this study is the subject of the study are students of SD Budya Wacana Yogyakarta who participate in extracurricular basketball. The sample used in the study was 15 male students and 15 female students. The instrument used is to measure Anthropometry including height, weight, and arm length and measure Shooting ability on students' Free Throw ability. Data analysis using a correlation test, namely the Regression Correlation test. The results of this study indicate that there is no significant relationship between body anthropometry and free throw shooting ability in basketball players at SD Budya Wacana Yogyakarta, with a significance value (2-tailed) of height with free throw shooting ability of 0.413 (0.413> 0.05), a significance value (2- tailed) of body weight with free throw shooting ability of 0.798 (0.798> 0.05), a significance value (2-tailed) of arm length with free throw shooting ability of 0.379 (0.379> 0.05). Together, the Sig. (2-tailed) value is 0.865, so there is no significant relationship between height, weight, and arm length with free throw shooting ability. The r2 value is 0.239, so the contribution is 23.9%, while the remaining 76.1% is influenced by other factors not examined in this study. So it can be concluded that there is no significant relationship between body weight and free throw shooting ability in basketball players at SD Budya Wacana Yogyakarta.